The Relationship Between Nursing Skills and the Accuracy of Triage Implementation in Patients at the Radjak Hospital Group Emergency Room - Ursula Arus Rinestaelsa; Ratna Mutu Manikam; Zahro Zukhairiah (Jurnal Kesehatan Masyarakat Perkotaan, 2025)
Background: Traffic accidents and other disasters are the main causes of death in urban areas, so that the knowledge and skills of nurses regarding the separation of patient types based on their emergencies are needed better, optimally and on target. The purpose of this study was to determine the relationship between nurse skills and the accuracy of triage implementation in patients in the Emergency Department. Method: This study used a correlation analytic research approach with a cross-sectional design. The population in this study was 37 respondents and the sample using total sampling was 37 respondents. The instruments of this study were observation sheets of nurse skills and triage implementation. The univariate analysis that will be calculated is gender, age, education, length of service, nurse skills, and triage implementation. While for the bivariate analysis, it is to relate nurse skills to the accuracy of triage implementation. Results: The results of this study using the ANOVA test and stated that there is a significant relationship between nurse skills and the accuracy of triage implementation obtained a p value of 0.0005 (ɑ<0.05). Conclusion: Most nurses working in the Emergency Room have high nursing skill scores and high triage implementation scores, so there is a relationship between nursing skills and the accuracy of triage implementation in patients. Emergency nurse triage skills focus on rapid assessment, patient categorization, and patient placement. Triage serves not only as a core skill but also as a tool for managing, monitoring, and evaluating patients and available resources.